2022
DOI: 10.15408/ijee.v9i1.26787
|View full text |Cite
|
Sign up to set email alerts
|

English Blended Learning: An Analysis of Indonesian Students’ Perception

Abstract: The study attempted to analyze the students of Tadulako University's perspective toward blended learning instruction in English teaching. The study employed a quantitative approach using a longitudinal survey design. 48 English department students in the fourth and sixth semesters were selected as the sample of the research using a simple random sampling technique. The data were gained through the questionnaire distributed online and the interview in the face-to-face technique. Data have been analyzed descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The first challenge found in this study was mainly found by students who live in a geographical condition with unstable internet networks, particularly in Central Sulawesi (Syafri&Saude, 2022). In line with Suriaman et al (2022), the surveyed students also showed the severe drawbacks of blended learning (LMS Platform based), such as defective materials, login problems, low creativity in searching for knowledge, and internet connection problems. Nevertheless, these drawbacks seemed to occur in different places.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The first challenge found in this study was mainly found by students who live in a geographical condition with unstable internet networks, particularly in Central Sulawesi (Syafri&Saude, 2022). In line with Suriaman et al (2022), the surveyed students also showed the severe drawbacks of blended learning (LMS Platform based), such as defective materials, login problems, low creativity in searching for knowledge, and internet connection problems. Nevertheless, these drawbacks seemed to occur in different places.…”
Section: Discussionmentioning
confidence: 75%
“…In particular, Zainuddin et al (2019) found that video lectures posted by lecturers evoke students' interest in online learning. The benefit of blended learning(LMS Platform based) is reliable and widely recognized (Suriaman et al, 2022). This result may imply that providing exciting content and valuable materials uploaded by lecturers in LMS may facilitate students' motivation to learn and help them understand taught courses and eventually obtain satisfactory learning results.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Fitri and Rifa'at (2021) suggested teacher's empowerment through ICT and emphasized on teachers' workplace training, seminar etc. Another study found Moodle-based instruction and in-person learning very convenient (Suriaman, A., Tadeko, N,. Manurung, K., Usman, S., & Yuliyani, A., 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some activities can be done collaboratively using some applications in a smartphone. Thus, students can interactively exchange information with other users (Suriaman et al, 2019). In other words, the students can be more involved in that learning process.…”
Section: Benefit and Limitations Of Smartphone-assisted Language Lear...mentioning
confidence: 99%